Kinetic disruption of lipid rafts is a mechanosensor for phospholipase D - E. Nicholas Petersen (Nature Portfolio, 2016)
Mechanosensation by biological membranes can be relayed by mechanical tension to ion channels. Here the authors show that phospholipase D (PLD) is activated by mechanical disruption of lipid rafts which allows PLD to mix with its substrate in the lipid membrane, and propose a kinetic model of force transduction.